The essential role of language in survey research - Mandy Sha (RTI Press Publication, 2020)
Language users, such as survey respondents and interviewers, must speak the same language literally and figuratively to interact with each other. As diversity grows in the United States and globally, interviewers and respondents may speak a different language or speak the same language differently that reflects their own cultural norms of communication. This book discusses the role of language in survey research when comparisons across groups, cultures, and countries are of interest. Language use in surveys is dynamic, including words, symbols (e.g., arrows), and even emojis. The entire survey life cycle is carried out through language. Researchers write or translate questions and instructions that will address research questions and then pretest them using various techniques, including qualitative inquiry that focuses on context beyond just "the numbers." Human or virtual data collectors use persuasive messages to communicate with survey respondents and encourage their survey participation. Respondents must comprehend and interpret survey questions and instructions to provide a response. All of these survey processes and products contribute to data quality, and the role of language is essential.